Zeolitic imidazolate framework ZIF-67 grown on NiAl-layered double hydroxide/graphene oxide as cathode catalysts for oxygen reduction reaction in microbial fuel cells. (15th October 2022) - Chen, Junfeng; Yang, Jiaqi; Wang, Xuemei; Yang, Daoxin; Wei, Qingying; Wang, Yongle; Wang, Renjun; Liu, Yanyan; Yang, Yuewei
Abstract: In this study, the cathode catalysts for microbial fuel cells (MFCs) were successfully synthesized by two-step feeding method. NiAl-layered double hydroxide (LDH) nanoparticle was attached efficiently on the surface of graphene oxide (GO) in situ, zeolitic imidazolate framework (ZIF-67) was modified on LDH surface layer; Highly crystalline NiAl-LDH/GO@ZIF-67 composite was flawlessly prepared, nano-hybrid had (003), (006), (011), (112) and (222) characteristic crystal planes attribute to NiAl-LDH/GO and ZIF-67 by X-ray diffraction (XRD), and the sheet-like structure and polyhedral structure were observed. The NiAl-LDH/GO@ZIF-67 nano-hybrid was rich in metal elements and provides a wealth of electrochemical active sites by EDS test. The study displayed that the maximum output voltage of NiAl-LDH/GO@ZIF-67-MFC was 516 mV and the stabilization time could last for about 8 d. The maximum output power was 501.26 mW/m 2, which was 1.31 times of NiAl-LDH/GO-MFC (381.92 mW/m 2 ) and 2.76 times of ZIF-67-MFC (181.48 mW/m 2 ). The GO with high conductivity was used as the substrate to ensure the stability of electrode cycle and the efficiency of power generation, the laminar structure of NiAl-LDH provided the specific surface area for the reaction, which facilitated the transport of electrons. The good structure of ZIF-67 increased the active sites of the composite. The excellent properties of the composites promoted the electrochemical stability and electricity production output of MFC. This study provided a method for the further application of MFC in the wastewater field. Graphical abstract: Image 1 Highlights: ZIF-67 was grown on NiAl-LDH/GO by simple two step hydrothermal method. NiAl-LDH/GO@ZIF-67 as MFC cathode had preeminent stability and persistence. Maximum power density produced by MFC was 501.26 mW/m 2 .